2022
DOI: 10.28991/esj-2022-sper-017
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Students’ Academic Performance in Selected Mechanical Engineering Courses Prior-to-and-During COVID-19 Era

Abstract: Advances in Information and Communications Technology (ICT) as well as the present challenges of COVID-19 have led to a new paradigm causing an absolute or partial transition from in-person classroom teaching-learning to online. There is little information available on research efforts that investigated the impact of an online learning approach on the academic performance of students in mechanical engineering-based courses. Therefore, the objective of this paper is the impact study of online learning mode as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…After the outbreak of the COVID-19 virus in 2020, a total lockdown became necessary in many countries (Mboera et al, 2020 ). The COVID-19 lockdown was accompanied by a decline in physical business, academic, and tourist activities around the world (Oyewola et al, 2022 ; Pahrudin et al, 2021 ). Consequently, it is important to explore whether the reduced human activities evident during the COVID-19 lockdown are affecting the concentration, distribution, sources, and potential health risks of PAHs across all areas in Onne, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…After the outbreak of the COVID-19 virus in 2020, a total lockdown became necessary in many countries (Mboera et al, 2020 ). The COVID-19 lockdown was accompanied by a decline in physical business, academic, and tourist activities around the world (Oyewola et al, 2022 ; Pahrudin et al, 2021 ). Consequently, it is important to explore whether the reduced human activities evident during the COVID-19 lockdown are affecting the concentration, distribution, sources, and potential health risks of PAHs across all areas in Onne, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the structure that online learning has, students report feeling more motivated when they see a general preview of the course and when they can predict what is going to be next in their course since they have a greater possibility of planning [42]. It has also been shown that synchronous classes should not last more than 45 minutes to provide better levels of attention and concentration and that the degree of attractiveness of the online course is highly conditioned by the presence of high-quality audiovisual content, gamified activities, and feedback spaces [42,[45][46][47].…”
mentioning
confidence: 99%